Akibat Hukum terhadap Kekuatan Eksekutorial Sertifikat Hak Tanggungan dalam Hal Objek Jaminan Musnah karena Bencana Alam - Prastika, Kadek Septian Dharmawan; Budiartha, I Nyoman Putu; Styawati, Ni Komang Arini (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
This research is motivated by legal issues arising from the destruction of collateral objects under land mortgage rights, due to natural disasters, which renders the executorial power of the mortgage certificate unenforceable and creates legal uncertainty for creditors. The research problems include identifying the forms of legal protection available to creditors and determining the legal consequences for the executorial power of the mortgage certificate when the collateral object is lost. The objective of this research is to analyze both preventive and repressive legal protections for creditors and to explain the shift in the creditor’s position from a separatist creditor to a concurrent creditor pursuant to Article 1131 of the Civil Code. The research provides theoretical benefits by enriching the study of security law and practical benefits by offering guidance for banking institutions, notaries, and policymakers. The method employed is normative legal research using statutory, conceptual, and case approaches, with qualitative analysis of legal materials. The findings indicate that the destruction of the collateral object eliminates the creditor’s ability to execute the collateral through parate execution however, it does not extinguish the creditor’s claim against the debtor, which may still be pursued through general guarantees and alternative protection mechanisms such as insurance claims or substitute collateral. The conclusion of this research emphasizes the need for specific regulation regarding the risks associated with the destruction of collateral objects. The recommendations include mandating insurance coverage, improving relevant regulations, and enhancing risk-mitigation efforts by creditors.